Resistance of tropical maize inbreds to major virus and viruslike diseases - Brewbaker, J.L.; Kim, S.K.; Logrono, M.L. (1991)
Tropically-adapted maize inbreds of high combining ability were evaluated internationally for general resistance to seven virus and virus-like diseases, all insect-transmitted. Replicated trials under controlled viral epibiotics were conducted at five locations as part of the collaborative Maize Inbred Resistance project. The viruses and testing sites included CS (corn stunt mollicute complex) in Mexico, MBSDV (maize black-streaked dwarf virus) in Korea, MCDV (maize chlorotic dwarf machlovirus) in Ohio, MDMV (maize dwarf mosaic potyvirus strain A) in Hawaii and Ohio, SCMV-MB (sugarcane mosaic potyvirus MB) in Ohio, MMV (maize mosaic potyvirus) in Hawaii and MSV (maize streak geminivirus) in Nigeria. Over 100 open-pedigree inbreds, largely of tropical origin, were scored empirically to each virus and ranked on the basis of mean values for all entries. A relatively high proportion of the inbreds showed high or moderate resistance to MDMV-A (49%), MMV (42%) and SCMV-MB (33%), while fewer were resistant to CS (23%) and MSV (17%). Very few showed resistance to MBSDV and none to MCDV, both temperate viruses. Few inbreds showed combined resistance to more than two viruses. Only four instances of significant resistance correlations occurred, notably between the related potyviruses MDMV-A and SCMV-MB (r = 0.49). Resistance was derived primarily from regions where each virus was originally endemic.